Where Science Meets Users Needs: Storm Surge in Eastern NC - Munroe, Robbie (East Carolina University, 2019)
The coast is well researched because of its intrinsic value to visitors, the lives and property of those who live at the coast, and the environmental services it provides through tourism, natural resources, and as a natural barrier to waves, wind, and water. Storm surge coupled with wave energy at the coast is partly responsible for shaping or damaging coastlines including both natural and human built environments. This dissertation work explores the storm surge hazard focused across Eastern North Carolina through three standalone but related chapters. Storm surge at longer lead times is explored through the examination of climate oscillations related to storm surge characteristics (chapter one) and the synoptic conditions responsible for storm surge (chapters one and three). Emergency support personnel's desire for different types of surge information as well as surge information at longer lead times is covered in chapter two. Statistical and synoptic climatology results indicate a significant relationship between a combination of water height and duration with climate oscillations, which show promise in enhancing the forecasting and awareness of storm surge at greater lead times to further meet storm surge users' needs.
Keywords: Coastal storms; Flooding; Tropical cyclone; Extratropical cyclone; Emergency manager; Storm surges--North Carolina; Emergency communication systems--North Carolina; Synoptic meteorology--North Carolina; Climatology